Civic Education for the Planet: Cross-National Trends of Ecological Citizenship and Strategies for Advancing SDGs - Elda Dwi Pratiwi; Leni Anggareni; Sri Wahyuni Tanshzil; Rahmat Rahmat; Istifadah Istifadah (Jurnal Pendidikan Progresif, 2026)
This study aims to map research trends on ecological citizenship and identify ecological-based citizenship education strategies in building citizens' ecological awareness. The environmental crisis and the global need for sustainable development emphasize the concept of citizenship not only as a legal status and as formal political participation, but also as a responsibility that binds humans to a democratic community and to a life-sustaining ecology. This study used a systematic literature review and bibliometric analysis method following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Data were collected from the Scopus database from relevant articles published between 1998 and 2025. Based on inclusion and exclusion criteria, 155 articles were deemed eligible for analysis. Bibliometric analysis was conducted using VOSViewer to visualize bibliographic data. The research findings show that studies on Ecological Citizenship are mostly centered on studies on the environment, politics, and development policies. Few studies highlight environmental awareness education within citizenship education. This study identifies five important findings regarding ecological citizenship education strategies that can be developed, including through i) curriculum; ii) pedagogy; iii) school movement; iv) social action; and v) digital citizenship. This study concludes that the study of ecological citizenship throughout 1998-2005 experienced dynamic growth and a significant increase, coinciding with the growing attention to green values, sustainability issues, and citizens' ecological responsibilities. However, the pedagogical perspective in Civic Education is relatively marginal. This study provides a strong foundation for future Civic Education to develop a learning model that emphasizes the harmonization of citizens' rights and obligations not only towards the state and fellow citizens, but also towards the universe. So that Civic Education can prepare citizens who have ecological awareness and support sustainable development. Keywords: civic education, ecology awareness, ecological citizenship, environment education, SDGs.